The Strategic Role of Relationship Marketing in Sustaining Long-Term Customer Value: Evidence from Customers in Yogyakarta - Salamatun Asakdiyah (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study aims to analyze the strategic role of relationship marketing in sustaining long-term customer value among customers in Yogyakarta. A quantitative approach with an explanatory research design was employed. Primary data were collected through questionnaires distributed to 160 respondents selected using purposive sampling. Respondents were at least 17 years old, had purchased or used the company’s products or services at least twice within the last six months, and had experience interacting with the company through direct or digital channels. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that relationship marketing has a positive and significant effect on customer trust and customer satisfaction, both of which positively influence customer loyalty. Customer loyalty, in turn, significantly affects long-term customer value. Relationship marketing also directly influences long-term customer value, although indirect effects through trust, satisfaction, and loyalty provide stronger explanations. These findings confirm that relationship marketing is a strategic approach for building valuable long-term relationships. The study contributes to relationship marketing, commitment-trust, and customer value theories while providing managerial implications for sustaining business performance in competitive markets.